Climate change and rural institutions in Central Viet Nam - Le Duc Ngoan; Le Thi Hoa Sen; Nguyen Thi Thanh Huong; Ian Christoplos; Lily Salloum Lindegaard (Danish Institute for International Studies (DIIS), 2013)
This working paper presents an overview of initial findings regarding the factors influencing how meso level institutions in Central Viet Nam are responding to climate change and extreme climate events. Findings focus on the challenges affecting coastal zones, particularly areas which are impacted by a combination of environmental change and the introduction of new livelihood opportunities, including rapidly expanding aquacultural production. The working paper describes emerging policies and trends in institutional response to climate change, with emphasis on the convergence of this response with disaster risk management and broader development efforts. The working paper highlights a fundamental contrast between structures related to the current concrete manifestations of climate change, primarily flood and storm control, and the future scenarios of climate change.
Keywords: 300